Analiza potencjału przedsiębiorczego województwa podkarpackiego - Strojny, Jacek (Przedsiębiorczość - Edukacja, 2010)
The article is concerned with one of the fundamental aspects of economic systems developmentin European integration and globalization contexts. It deals with the development ofentrepreneurial potential in the Podkarpackie region. To explain the course of this process theauthor uses a model of entrepreneurial analysis that includes four levels: individual entrepreneurship,community entrepreneurship, organizational entrepreneurship and economy entrepreneurship.In the description of all these levels a measurement methodology is suggested.It is also important that the evaluation of entrepreneurial potential takes place on the mobilecapital market. Territories (countries, regions, etc.), that offer better opportunities to develophave a greater chance of attracting mobile capital. Consequently, they can accelerate the developmentprocesses. Of course, administrative units that do not achieve economic and socialprogress do not attract external capital, and they cannot come out from stagnation despite theequalization mechanism both at domestic and European Union level.On the base of this consideration the author analyzes the situation in the Podkarpackie voivodshipin the terms of development opportunities in both the context of global and Europeanintegration. He attempts to specify the development potential in the area of entrepreneurialgrowth by using his proposal of models. To achieve this goal he uses statistical data and theresults of a questionnaire that he himself conducted. Clearly, the article is not a complete diagnosisof the situation in the region as this would require a far more comprehensive publicationand more in-depth research. This means that the rate of potential growth in the article are notcomprehensive, and they may demand supplementation. Nevertheless, they can be used toformulate some useful conclusions and judge the situation accordingly.